THE SHIFT FROM LANGGAR TO MADRASA: CONTESTATION AND INSTITUTIONAL TRANSFORMATION OF ISLAMIC EDUCATION IN SOUTH SULAWESI (1900–1942) - Chaerul Mundzir; Susmihara; Hasaruddin; Muhammad Husni; Sitti Nurunnisa Maulida A (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
This article explores the transformation of Islamic education in South Sulawesi from the traditional langgar system to the more structured form of madrasah during the period 1900– 1942. The study aims to identify the social, political, and religious dynamics that underpinned the shift in Islamic education amidst Dutch colonial pressures and Christian missionary expansion. Utilizing a historical approach and descriptive-analytical method, this article provides a historical account of the emergence of madrasahs as both an adaptive response to modern challenges and a form of resistance to the hegemony of colonial education. The findings reveal that madrasahs were not merely a continuation of traditional langgar, but also institutional innovations that integrated elements of modernity, such as graded systems, structured curricula, and academic evaluations, while maintaining the core values of Islamic teachings. Madrasahs became ideological and cultural arenas of contestation between Islamic and secular colonial educational systems. Local scholars such as Anregurutta Sulaiman and H. Muhammad As’ad played crucial roles in establishing and developing madrasahs in regions like Sengkang, Bone, and Luwu. This article concludes that the transformation of Islamic educational institutions reflects the Muslim community’s endeavor to preserve religious identity and create a competitive educational foundation within the colonial structure.